Liver structure and function following small bowel resection. Issue 6 (June 1973) - Gupta, M. C.; Neale, Graham; Dowling, R. Hermon
Abstract : The observation that patients with extensive small bowel resection have impaired hepatocellular function with reduced BSP clearance and fatty change in biopsies from the liver led to a systematic study of liver structure and function following proximal and distal small bowel resection in the rat. While anaesthesia and surgery impaired BSP clearance per se, small bowel resection further reduced BSP clearance with impairment of both uptake and excretion phases of BSP excretion. The increased BSP retention was more marked after distal than after proximal small bowel resection, but in both experimental groups the abnormalities of BSP excretion spontaneously returned to normal three to four weeks after surgery. Circulating liver enzymes were normal but serum alkaline phosphatase was significantly depressed, particularly after distal resection. Isoenzyme studies showed that the depression of serum AP was due to a reduced intestinal isoenzyme. While serum levels remained consistently depressed up to eight weeks after proximal resection, in parallel with mucosal regeneration, serum AP returned to normal two to four weeks after ileectomy. While these minor changes in hepatic structure and function would normally be of little clinical importance, the additional insult of hepatic dysfunction may well be important in malnourished patients after extensive small bowel resection.